Removal of textile dye reactive blue 49 from wastewater and dye baths by membrane separation and subsequent photo-Fenton reaction, UV-C and UV-C/H2O2 - Krupková, Olga; Dušek, Libor; Cuhorka, Jiří; Soares, Graca; Vagenknecht, Gabriela; Mikulášek, Petr; Bendová, Helena (Elsevier Science BV, 2024)
The paper is focused on testing the two-phase treatment of wastewater from dyehouses and the production of aminoanthraquinone dyes using membrane separation and a subsequent advanced oxidation process with an efficiency >99.99 %. Commercial nanofiltration membranes AFC 30 and AFC 40 were used for the separation of Reactive Blue 49 dye. The effect of pressure difference, injection concentration, permeate flow intensity, etc. was studied. In all tested parameters, the dye was completely retained without fouling the membranes. The obtained data were interpreted using the film model and the two-parameter Spiegler-Kedem model based on nonequilibrium thermodynamics. The work contains a kinetic study comparing the rate of decolorization and subsequent mineralization of the dye using the photo-Fenton reaction, UV-C, and UV-C/H2O2. The effect of pH was also studied. In all reaction systems the dye chromophore was degraded with simultaneous quantitative decolorization of the model wastewater. Subsequently, the mineralization of the intermediates was studied through the decrease of total organic carbon. Its efficiency ranged from 35 to 82 % within 2 h from the start of degradation. After 7-12 h, depending on the conditions, the dye was already 87-99 % mineralized. The degradation pathway of the dye was proposed using LC-MS.
Odstranění textilního barviva reaktivní modři 49 z odpadních vod a barvicích lázní membránovou separací a následnou foto-Fentonovou reakcí, UV-C a UV-C/H2O2
Keywords: Reactive Blue 49; Photochemical decolorization; Mineralization; Nanofiltration; Textile dyes; Reaktivní Modř 49; Fotochemické odbarvování; Mineralizace; Nanofiltrace; Textilní barviva